Gene action for important fruit characters in brinjal (Solanum melongena L.) - Ansari, Abdul Majid; Singh, Y.V. (Annals of Agricultural Research, 2016)
Generation mean analysis was carried out to assess the presence of inter-allelic interaction and toestimate the importance of various gene effects for inheritance of six fruit characters in brinjal viz.,fruit length, fruit diameter, average fruit weight, total number of fruits per plant, early yield perplant and  yield per plant. Six generations  of five families were used for the study.  Family  wiseestimates of gene effects and type of epistasis were summarized for all six characters. Scaling testrevealed that all four types of scales (A, B, C and D) showed highly significant effect along with thehigh values of chi-square (χ2). Both tests (scaling and chi-square) proved that the six parametermodels were adequate for the estimation of gene effects. The joint scaling tests for these charactersshowed varied values of gene effects in families for all types of gene effects viz.  Additive  (d),dominance (h), additive x additive (i), additive x dominance (j) and dominance x dominance (l)  fordifferent traits. Almost all characters showed duplicate dominance type of epistasis. Based on theseresults, inter-mating among selected individuals through recurrent selection and diallel selectivemating system could be an alternative method for improvement of these traits of brinjal.